The HR Management Perspective on the Elimination of Mandatory Retirement in Ontario - Templer, Andrew; Armstrong-Stassen, Marjorie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
Effective as of December, 2006, an end to mandatory retirement was legislated in Ontario. Prior to this move, some employers and labour organizations were opposed to eliminating mandatory retirement and expressed concern about the negative impact such a move would have on business and on individual workers. This exploratory descriptive study examines HR managers’ (N = 415) perceptions of the impact of the elimination of mandatory retirement in Ontario. Compared with HR managers in organizations not practicing mandatory retirement, HR managers in organizations with a mandatory retirement policy reported their organization had significantly fewer HR practices in place tailored to older employees and would be significantly more likely to respond to the elimination of mandatory retirement by implementing new HR practices or by modifying existing HR practices.